Homes and gardens decorating : - Kime, Giles (Conran Octopus Ltd, 2006)
Published in association with the UK's leading interior design magazine, here is the definitive guide to home decorating, from planning it out, to the nuts and bolts of getting it done. Includes case studies, profiles of classic and contemporary styles, and more than 250 full-color photos. Contents Include: Finding A Style; Planning; Color, Pattern & Texture; Walls & Ceilings; Flooring; Fabric & Upholstery; Room Solutions; The Knowledge.